Alleviation of copper toxicity using the combined application of silicon and arbuscular mycorrhizal fungi in cucumber - Jayathilaka, Mevuni Sarada; Datta, Avishek; Himanshu, Sushil Kumar; Zulfiqar, Farhad; Asian Development Bank-Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
In agricultural soils, higher concentrations of copper (Cu) have accumulated above the allowable limits (100 mg kg 1 ) due to heavy use of Cu containing fungicides, pesticides and organic fertilizers. Copper toxicity is proven to induce nutrient imbalances in plants, containing plant growth. An experiment was conducted in the polyhouse of Department of Food, Agriculture and Bioresources, Asian Institute of Technology, Bangkok, Thailand) from September 2023 to January 2024.Cucumber (Variety Keaw Siam) was transplanted with pots filled with 16 kg soil. Control, 75,150,300 and 600 mg kg-1 of soil Cu was maintained. Two silicon (Mono Silicic Acid) levels and two levels of Arbuscular Mycorrhizal Fungi (AMF) were maintained as no AMF and with AMF (12 g pot 1 ). Eighty pots were arranged in completely randomized design. Highest growth, yield and photosynthetic rates were reported in the copper level 75mg kg-1 with Si and AMF. The growth and yield of cucumber showed a decreasing trend starting from the 150 mg kg-1 soil Cu. According to the results, it is evident that the combined application of Si and AMF was more beneficial on alleviating copper toxicity in cucumber rather than individual application of AMF and Si. The effect of AMF and Si on alleviating Cu toxicity was more pronounced in the Cu levels 300 mg kg-1 and 600 mg kg-1. The increased potential of using combined application of Si and AMF for alleviation of Cu toxicity must be due to improved Si absorption by plant associated with AMF, which increased plant{u2019}s ability to resist Cu toxicity stress through cumulative positive impact.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Agricultural Systems and Engineering
Thesis (M. Sc.) - Asian Institute of Technology, 2024
Keywords: Vesicular-arbuscular mycorrhizas; Mycorrhizal fungi; Cucumbers; Copper -- Toxicology